Site Engineering for Landscape Architects - Strom, Steven (New York Academy of Sciences Ser., 2013)
Of Critical Constraints -- 3: Contours and Form -- Definition -- Constructing a Section -- Characteristics of Contour Lines -- Contour Signatures and Landform -- Ridge and Valley -- Summit and Depression -- Concave and Convex Slopes -- Uniform Slope -- Grade Change Devices -- Case Studies -- Olympic Sculpture Park -- Gasworks Park -- Olympic Park -- 4: Interpolation and Slope -- Topographic Data -- Interpolation -- Interpolation Between Contour Lines -- Calculating Slope -- Slopes Expressed as Ratios and Degrees -- Slope Analysis -- Computers and Terrain Analysis